Empowerment of coffee farmers in Gunung Manik Village through intercropping of honey bee (apis mellifera) - Aan Kunaedi; Elva Angela (Community Empowerment, 2024)
The potential for utilizing the natural resources of Gunung Manik Village remains largely untapped. Abundant natural commodities such as coffee, cloves, cardamom, and others are available. Utilizing land through intercropping in coffee plantations provides dual benefits for farmers, including beekeeping of Apis Mellifera species. The goal of community empowerment is to develop the natural potential through honey cultivation found in the forests of Gunung Manik Village. The method used involves workshops for training in beekeeping management, honey harvesting, and the transfer of Apis Mellifera forest bee colonies into honey bee cultivation boxes in coffee plantations. The outcome of this activity is an increase in the understanding and skills of residents in harvesting forest honey and transferring bee colonies into cultivation boxes.